Development of Interactive E-Modules Using Canva and Heyzine Flipbook to Improve the Learning of Grade VII Junior High School Students - Darmansyah; Eva Roza Mesra; Ramalis Hakim; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2025)
The education system needs to integrate technology as a means to improve the quality of learning and prepare students to face the challenges of the 21st century. Technology-based learning is now a solution for creating a more interactive, flexible, and accessible learning experience anytime and anywhere. This research focuses on the development and evaluation of an E-Module based on Canva and Heyzine Flipbook for enhancing the learning process in Materi for 7th-grade students at SMPN 1 Lubuk Alung. The study utilized the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to guide the development of the E-Module. The results of the validation process indicated that the E-Module is "very feasible" with a validation score of 88%. During the implementation phase, the E-Module was tested on 32 students, with practical use evaluations from both teachers and students yielding scores of 96%, indicating its high practicality. The effectiveness of the E-Module was assessed through pre- and post-tests, with the average score improving from 63 to 84, resulting in a significant Ngain value of 0.55, indicating high effectiveness. This research concludes that the Canva-based E-Module using Heyzine Flipbook is an effective, practical, and feasible tool for improving cognitive learning outcomes in Materi education.